Analysis of Eye Disease Classification by Comparison of the Random Forest Method and K-Nearest Neighbor Method - Meidelfi, Dwiny; Hendrick; Sukma, Fanni; Kharisma, Srintika Yunni (SOTVI, 2023)
Eye disease is a serious issue all over the world, and image-based classification systems play an important role in the early detection and management of eye disease. This research compares the performance between Random Forest (RF) and K-Nearest Neighbor (KNN) classification models in identifying eye disorders using image datasets divided into four classes: